2022
DOI: 10.3390/nano12030488
|View full text |Cite
|
Sign up to set email alerts
|

On-Surface Thermal Stability of a Graphenic Structure Incorporating a Tropone Moiety

Abstract: On-surface synthesis, complementary to wet chemistry, has been demonstrated to be a valid approach for the synthesis of tailored graphenic nanostructures with atomic precision. Among the different existing strategies used to tune the optoelectronic and magnetic properties of these nanostructures, the introduction of non-hexagonal rings inducing out-of-plane distortions is a promising pathway that has been scarcely explored on surfaces. Here, we demonstrate that non-hexagonal rings, in the form of tropone (cycl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…(b) Schematic representation of the reaction pathway toward the formation of chevron graphene nanoribbons on Au(111), and the constant height frequency-shift nc-AFM image. 64…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) Schematic representation of the reaction pathway toward the formation of chevron graphene nanoribbons on Au(111), and the constant height frequency-shift nc-AFM image. 64…”
Section: Discussionmentioning
confidence: 99%
“…We showed that cycloheptatrienones are thermally transformed on-surface by decarbonylation and intramolecular rearrangements (Figure 5b ). 64…”
Section: Molecular Electronics and On-surface Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While armchair GNRs (aGNR), and in particular 7-aGNR obtained from 10,10′-dibromo-9,9′-bianthracene, represent by far the most studied GNR type, chevron GNRs (cGNRs) based on 6,11-dibromo-1,2,3,4-tetraphenyltriphenylene (precursor 1 , Figure ) have also attracted particular attention. They have been extensively studied experimentally as well as theoretically, , also by considering atomic modifications such as the introduction of heteroatoms or the addition of bulky edge groups. , While most of these studies highlight the interest of GNR as a final product, the on-surface growth process and the different intermediate states, leading to the GNR formation have been only scarcely studied and rarely systematically addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are only a few reports discussing the on-surface formation of non-benzenoid moieties, 18,[25][26][27][28][29] sometimes in conjugated polymers. 8,21,[30][31][32][33][34][35] Most of them have utilized strategies based on oxidative ring closure, 8,36 bond rotation 37 or the use of molecular precursors with embedded 5-membered rings. 38,39 Therefore, it is highly desirable to provide new strategies that allow the controlled formation and detailed analysis of such non-benzenoid molecules.…”
Section: Introductionmentioning
confidence: 99%